Nepal’s Educational System and Its Impact on Policy and Governance: An Editorial (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
This editorial reviews the education policy and governance of Nepal’s government through a systematic meta-analysis of nationally and internationally published research, reports, and archival data. The methodology involves comprehensive collection and evaluation of scholarly articles and official documents to provide an integrated assessment of policy frameworks and governance structures. Findings indicate that Nepal’s 2015 Constitution guarantees up to 12 years of free education in public schools, complemented by the establishment of over eleven universities, including Tribhuvan University, Mahendra Sanskrit University, Purbanchal University, Lumbini Buddhist University, Agriculture and Forestry University, and others. The Nepalese education system comprises three main tiers: secondary education up to grade 12 emphasizing practical market-linked skills; mid-level bachelor’s and master’s programs aimed at human resource development for various sectors; and advanced studies producing high-level professionals such as researchers and planners. Despite extensive university expansion, challenges remain in technical institutes’ educational quality. The study recommends enhancing market-driven education and entrepreneurship integration across all levels to better prepare Nepal’s youth for independent employment and innovation.